Characterization of solid perfume based on Cocoa Butter with Jasmine Oil as fragrance. Issue 1 (January 2021) - Septiyanti, Melati; Meliana, Yenny; Suryani, Novia; Hendrawati,
Abstract: Cocoa butter can be obtained from by-product of chocolate powder processing from the result of mechanical pressing using hydraulic press. As a source of vitamin E, cocoa butter in cosmetic has some advantages which are to soften and moisturize the skin. Meanwhile, jasmine can be used as a fragrance in perfume and cosmetics. In this study, cocoa butter was used as raw material for solid perfume. Its optimal concentration in the product was determined. Solid perfume was made by melting cocoa butter and beeswax at 90°C followed by adding jasmine oil as fragrance. The formulation variation of solid perfume was done with cocoa butter concentration 10%, 20%, 30%, 40% and 50% (w/w) and addition of patchouli oil as fragrance fixative agent. The following tests were carried out on the products: functional group analysis, hardness test, homogeneity test, physical stability test, melting point test, antioxidant test, and organoleptic test. The result showed that the variation of cocoa butter concentration affected the physical characteristics of the solid perfume. The optimum product of solid perfume based on panelists' organoleptic test was achieved with cocoa butter concentration of 30%. It had an organoleptic score of 3.63, antioxidant activity with IC50 value of 201.98µg/mL, hardness penetration 14.16 mm/second, melting point 90°C and pH value 4.